Evaluation of Leukocyte Esterase Reagent Strips in Rapid Bedside Diagnosis of Spontaneous Bacterial Peritonitis - Wangdi Sherpa, Tshering; Koirala, Dinesh; Gyawali, Susmita (Nepalese Medical Journal, 2025)
Introduction: Spontaneous bacterial peritonitis is defined as an ascitic fluid infection without an evident intra-abdominal surgically treatable source. Spontaneous bacterial peritonitis is one of the severe complications in patients with cirrhosis and ascites. Without early antibiotic treatment, this complication is associated with a high mortality rate. The leukocyte esterase dipstick test can rapidly diagnose spontaneous bacterial peritonitis. The study was done to evaluate the diagnostic accuracy of the leukocyte esterase dipstick test for the diagnosis of spontaneous bacterial peritonitis. Materials and Methods: This was a cross-sectional, prospective study. Paracentesis was performed on admission. The ascitic fluid obtained at bedside was immediately tested with a reagent strip. Ascitic fluid was then analyzed for neutrophil cell count. The result of the reagent strip was compared with the ascitic fluid cell count for the determination of the sensitivity, specificity, positive predictive value, and negative predictive value of the test. Results: A Total of 76 patients were enrolled in this study. Leukocyte esterase reagent strip correctly detected 23 (51%) positive and 45 (42.6%) negative cases of SBP. The sensitivity, specificity, positive predictive value, negative predictive value of the leukocyte esterase dipstick test to diagnose spontaneous bacterial peritonitis were 88.46%, 90%, 82.14% and 93.75% respectively. Conclusions: The leukocyte esterase dipstick test can be used as a rapid test for the diagnosis of spontaneous bacterial peritonitis due to its high diagnostic validity.